Application of stable FEM-FDTD hybrid to scattering problems. - Rylander, T.
A recently developed, stable, finite-element method (FEM), finite-difference time-domain (FDTD) hybrid that eliminates the staircase approximation of complex geometries is tested by convergence studies for radar cross-sections. For a conducting sphere, 1 dB accuracy in all directions is obtained with nine cells per wavelength, whereas the NASA almond requires a higher resolution of about 15 cells per wavelength. For scatterers with a smooth boundary, the results converge quadratically with the mesh size, but for a horizontally polarized wave incident on the NASA almond, the order of convergence is lower because of singular fields at the tip
Keywords: FEM-FDTD hybrid; NASA almond; Conducting sphere; Electromagnetics modeling; Finite-difference time-domain analysis; Finite-element method; Mesh size; Radar cross-sections.; Scattering problems; Smooth boundary scatterers; Staircase approximation